Physiological demands of daily riding gaits in jockeys - Kiely, M. A.; Warrington, G. D.; Mcgoldrick, A.; O'loughlin, G.; Cullen, S. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Jockeys should maintain a high level of physical fitness to meet the physical demands of horse racing. The aim of this study was to determine the physiological requirements of the riding gaits used regularly in training. METHODS: Eleven trainee jockeys performed a maximal incremental Wattbike cycle ergometer test. Mean absolute and relative oxygen uptake (VO2) and heart rate (HR) were recorded for the steady-state period during a walk, trot and canter. Energy expenditure (EE) and associated metabolic equivalent (MET) were also estimated. RESULTS: During a walk, trot and canter, relative mean VO2 corresponded to 15±4%, 38±6%, 47±9% of VO2peak and mean HR corresponded to 48±6%, 60±6%, 71±7% of HRpeak respectively. Mean VO2 and mean HR were significantly different amongst gaits; P=0.001. Walking required the lowest estimated EE of 2.25±0.6 kcal.min-1 (P=0.001; 2.4 METs;) and it was significantly lower than trotting at 5.72±1.0 kcal.min-1 (P=0.001; 6.2 METs) and cantering at 7.10±1.8 kcal.min-1 (P=0.001; 7.7 METs). CONCLUSIONS: These riding activities are associated with relatively low physiological demand and alternate modes of exercise are recommended for trainee jockeys to ensure the demands of racing are met. Future research should investigate the physical training, both riding-specific and general conditioning, jockeys perform in preparation for racing.